MSME Development Strategy to Improve Competitiveness in the Digital Era and Product Innovation of MSMEs Desa Belawa - Budianto, Erwin; Hasanah, Ananda Putri; Lugina, Wenda Surya; Trisnawati, Titin; Cantika, Erly (Journal of Bussines Management Basic, 2024)
In the Thematic Real Work Lecture (KKN-T) the group of 53 conducted research on the Village Owned Enterprises (BUMDES) Manisan Cikuya (Manciya) of Belawa Village, Lemahabang District, with the aim to develop product innovation and increase competitiveness in the current digital age. The activities of KKN-T are carried out by descriptive research method with qualitative approach accompanied by information from internal and external factors with the acquisition of relevant y/y data in the form of packaging innovation, innovation of product results and expansion of marketing network. In this packaging innovation develops creative new ideas in designing, selecting materials, as well as determining the packaging function of a product. During KKN-T's activities, we as students of KKN-T group 53 provided extension and mentoring of the venture. With this activity, hopefully it can benefit partners in developing their business